Congenital malformations in children of epileptic pregnant women in the Cienfuegos province (2008-2018) - María Soledad Vilches León; Carmen Niurka Piña Loyola; Maylé Santos Solís; Vivian Rosa Vázquez Martínez; Cristóbal Jorge Torres González; Niurys Gonzales Cano (Medisur)
Background: in pregnant women, epilepsy is one of the most frequent neurological disorders, considered high risk due to the complications it produces. The probability of congenital malformations is higher in the descendant of these patients than in women who are not. Objective: to determine the risk factors associated with congenital malformations in children of epileptic pregnant women. Methods: a descriptive study of unpaired cases and controls was carried out, taken from the total number of epileptic pregnant women registered with fetuses or newborns in the period 2008-2018, in the Cienfuegos province. The sample was a group of cases: epileptic pregnant women with fetuses or newborns with congenital malformations (20); and a control group: taken from the total of epileptic pregnant women with healthy newborns (40). Information was required from the congenital malformations registry from the Archive department, of the Dr. Gustavo Aldereguía Lima hospital. Results: age over 35 years represented a four times higher risk (OR=4.3) for the presence of congenital malformations in these epileptic pregnant women. The history of genetic termination of pregnancy was statistically significant (p= 0.006) and increased the risk of having a malformation 16 times. Cardiovascular malformations were the most frequent, followed by renal and nervous. According to their classification and presentation, the largest and isolated prevailed, respectively. Conclusion: the risk factors associated with congenital malformations in children of epileptic mothers were: maternal age over 35 years, history of previous pregnancy with malformation and genetic interruption of pregnancy.